The Concept of Analysis in the Philosophy of Logical Empiricism - Nekrašas, Evaldas (Problemos, 1980)
The treatment of the question of origins of the concept of analysis in logical empiricism concerns certain aspects of the concept of analysis in classical empiricism and its modification at the beginning of the 20th century. Relations of logical and linguistic concepts of analysis are also discussed. The significance of analysis seen as a means of the adjustment of the framework of logical empiricism to the purification and unification of science is considered. In this connection, the role of Carnap’s principle of tolerance is found to be in the promotion of the process of self-destruction of applied logical empiricism. Though the primary aims that were supposed to stem from the application of logical analysis appeared to be illusory, the perfection of the method of analysis in the process of logical empiricism stimulated the rise and development of the logical theory of scientific knowledge and cognition.